Inappropriate habits of antibiotic use among medical specialists and students in Vilnius - Barkus, Artūras; Lisauskienė, Ingrida (Acta medica Lituanica, 2016)
Introduction. The resistance to antibacterial drugs is an emerging worldwide problem. Numbers of inappropriate ways to use antibiotics contribute to this issue. Self-medication is one of them. This study seeks to find out how prevalent the self-medication with antibiotics, their storage at home and the inappropriate acquisition of antibacterial drugs are among medical specialists in Vilnius, Lithuania. Methods. A cross-sectional survey was conducted. To better identify the potential target groups, the respondents were classified according to their relation to medical care: physicians, other medical personnel, medical students and people, directly not related to medical care. Results. The overall actual self-medication with antibiotics rate was 4.0%. And, although the actual self-medication rate might seem rather low, the intended self-medication rate was 51.4%. Also, a prevalent antibacterial drugs storage at home (45.8%) with a wide variety of preparations was reported. Only 61.9% respondents received prescriptions for antibiotics from their treating physician. 7.6% used the non-prescribed medicines and 22.0% received a prescription from a physician, who was either their colleague or a familiar person. Conclusions. Inappropriate habits of antibiotic use are prevalent. While there were some differences between the research groups, most of them were not statistically significant. It means that measures should be taken targeting health care givers as well as the general population. Educational programs about the rational use of antibiotics may help reducing the improper habits of antibacterial drugs usage, including self-medication. Encouraging the electronic drug prescription may be beneficial while reducing the prevalent inappropriate acquisition of antibiotics.